2017
DOI: 10.3390/ijms18040748
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine CXCL7 Heterodimers: Structural Insights, CXCR2 Receptor Function, and Glycosaminoglycan Interactions

Abstract: Chemokines mediate diverse fundamental biological processes, including combating infection. Multiple chemokines are expressed at the site of infection; thus chemokine synergy by heterodimer formation may play a role in determining function. Chemokine function involves interactions with G-protein-coupled receptors and sulfated glycosaminoglycans (GAG). However, very little is known regarding heterodimer structural features and receptor and GAG interactions. Solution nuclear magnetic resonance (NMR) and molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 64 publications
2
52
0
Order By: Relevance
“…In addition, it is known that CXCL7 forms heterodimers with other chemokines, e.g., CXCL1. This CXCL1/CXCL7 heterodimer interacts differently with GAGs compared to the CXCL7 monomer and the GAG-bound heterodimer cannot interact with the receptor (178). These data suggest that GAG interactions play a prominent role in determining heterodimer function in vivo.…”
Section: Consequences Of Cxcl5 and Cxcl7 Binding To Glycosaminoglycansmentioning
confidence: 87%
“…In addition, it is known that CXCL7 forms heterodimers with other chemokines, e.g., CXCL1. This CXCL1/CXCL7 heterodimer interacts differently with GAGs compared to the CXCL7 monomer and the GAG-bound heterodimer cannot interact with the receptor (178). These data suggest that GAG interactions play a prominent role in determining heterodimer function in vivo.…”
Section: Consequences Of Cxcl5 and Cxcl7 Binding To Glycosaminoglycansmentioning
confidence: 87%
“…Our future studies will address the relationship between dimer-tetramer equilibrium and GAG interactions. Recent studies have shown CXCL7 forms heterodimers with other platelet-derived chemokines ( 6 8 , 49 , 50 ), and that the heterodimer binds GAG with high affinity suggesting GAG interactions of both homodimers and heterodimers could regulate function.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that GAG binding is also driven by H-bonding interactions mediated by polar residues such as asparagine (Asn) and glutamine (Gln) (98,99). NMR and MD studies of several ELR chemokines suggest Asn and Gln are involved in GAG interactions (54,100). Considering these residues form weak H-bonds compared to lysines and arginines, the impact of mutating these residues on affinity, geometry, and neutrophil trafficking should give definitive insights into whether they play a role in defining specificity or affinity or both.…”
Section: Future Directions and Challengesmentioning
confidence: 99%